Coping tendencies and changes in athlete burnout over time - Madigan, D. J.; Rumbold, J. L.; Gerber, M.; Nicholls, A. R. (Psychology of Sport and Exercise, 2020)
Burnout can lead to numerous negative outcomes for athletes. While we know a reasonable amount about how athlete burnout develops over time, we know comparably less about the role of coping in this process. The present study aimed to help address this issue by examining the role of coping tendencies in predicting changes in athlete burnout over a six-month period. A sample of 141 junior athletes (mean age = 17.3 years) completed measures of coping tendencies (problem-focused and avoidance coping) and burnout. Participants also completed the measure of burnout on two further occasions, three months and six months after the initial assessment. Conditional latent growth curve modelling revealed that coping tendencies predicted changes in athlete burnout over time. In this regard, avoidance coping predicted increases in athlete burnout, whereas problem-focused coping was unrelated to changes in athlete burnout. These findings provide evidence that an athlete`s tendency to use avoidance coping strategies is linked to burnout development over time.